PREPARAÇÃO DA ZEÓLITA SODALITA VIA TRATAMENTO TÉRMICO, SUA IMPREGNAÇÃO COM ÍONS Zn2+ E UMA AVALIAÇÃO PRELIMINAR DE SUA EFICIÊNCIA NA PRODUÇÃO DE BIODIESEL - Kaminishikawahara, Katia Kaori (2015)
Biodiesel has great commercial potential for being biodegradable, non toxic, presenting low carbon monoxide (CO) emission and solid particles. It can be produced from the transesterification reaction of vegetal oil or animal fat as raw material. The optimization of the reaction speed in the biodiesel production is possible with the use of zeolites as catalysts that can be recovered at the initial level in an economical way. A field study was carried out to collect natural zeolites and to produce synthetic zeolites varying the amount of colloidal silica and sodium aluminate. The methodology which resulted in a zeolite with a single zeolitic phase and low amount of amorphous material was submitted to different thermal treatments (8, 12, 24, and 30 hours). The 24-hour thermal treatment obtained a zeolite (Sodalite) with high basicity which was impregnated with Zn2+ ions. The zeolitic material was characterized with X-ray diffraction (XRD), Rietveld method, thermogravimetry analysis (TG/DTG), infrared absorption spectrophotometry (IV), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), nitrogen physisorption analysis and basicity qualitative and quantitative analyses. The preliminary test converting soybean oil in alkyl esters was carried out employing non impregnated, impregnated with 3% and 9% Zn2+ ions and natural Sodalite. The non impregnated Sodalite was the one presenting the highest conversion rate (40.7%) possibly due to the larger number of total basic sites it presented. The low conversion rate verified in other tests might be ascribed to the saponification reaction, possibly due to its highly hygroscopic property which reduces the transesterification reaction efficacy. That is, the presence of absorbed water in the structure or the existence of Na+ and OH- ions enables triglyceride saponification reactions by taking water to the reaction medium.